Medical eligibility criteria for using various methods of contraception - V N Prilepskaya; E A Mezhevitinova; E L Sheshko (IP Berlin A.V., 2014)
Prevention of abortions and their complications - is priority task in the preservation of female reproductive health. Invaluable role here is played by rational contraception. The analysis of medical eligibility criteria for contraceptive methods is shown in this article.